2013
DOI: 10.1271/bbb.120670
|View full text |Cite
|
Sign up to set email alerts
|

New 3-<i>O</i>-Alkyl-4a,10a-dihydrofusarubins Produced by <i>Fusarium</i> sp. Mj-2

Abstract: Five new 3-O-alkyl-4a,10a-dihydrofusarubins (2-6) were isolated from the culture filtrate of a strain of Fusarium sp. (Mj-2), together with the known metabolite, anhydrofusarubin (1). The structures of the new metabolites were elucidated by spectroscopic analyses to be 3-O-butyl, 3-O-3'-methylbutyl, 3-O-2'-methylbutyl and 3-O-2'-phenylethyl-4a,10a-dihydrofusarubin A, and an isomer of 3-O-2'-phenylethyl-4a,10a-dihydrofusarubin A. Their antifungal and antibacterial activities were evaluated together with a 3-O-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Many active pharmaceutical compounds have been isolated from filtrates of Fusarium sp. cultures (Suzuki et al 2013). The leptosins I and J have been isolated from Leptosphaeria mycelium (Takahashi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Many active pharmaceutical compounds have been isolated from filtrates of Fusarium sp. cultures (Suzuki et al 2013). The leptosins I and J have been isolated from Leptosphaeria mycelium (Takahashi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These assignments were supported by the correlations of H-10a/C-1, C-4, C-4a, and C-5 as well as H-4a/C-10a, C-4, and C-5 in the HMBC experiments (Figure ). The magnitude of the vicinal coupling constant observed between H-4a and H-10a ( 3 J = 13.4 Hz) established a trans -diaxial relationship similar to those of dihydrofusarubin. The relative configuration of compound 1 was also confirmed by NOESY experiments and led to the assignment of the relative configuration of compound 1 as shown in Figure . The NOESY correlations of H-1 and H-4a with H-3 suggested that they were oriented on the same face of the preferred chairlike conformation (Figure ).…”
Section: Resultsmentioning
confidence: 67%
“…The 4a,10a-dihydropyranonaphthoquinones are a unique class of compounds and are commonly found in fungi and related microorganisms. Some of the 4a,10a-dihydropyranonaphthoquinones possessed potent biological activities, e.g., cytotoxicity and anti-HIV-1 and antibacterial activities. Dihydrofusarubin, a 4a,10a-dihydropyranonaphthoquinone derivative, is a secondary metabolite obtained from various species of Fusarium and exhibited antifungal activity . From our exhaustive search (SciFinder Scholar database), this work is the first report on the isolation of 4a,10a-dihydropyranonaphthoquinone derivatives from plants in the Ventilago genus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naphthoquinone and related metabolites are widely distributed in nature and have been found in various fungi. This class of compounds has attracted interest due to their broad range of biological action like insecticidal, antibacterial and fungicidal activity (Medentsev and Akimenko, 1998;Suzuki et al, 2013). Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%